Utilization patterns of Diploknema butyracea along the gradient of geography and culture in the Nepal Himalaya - Bhattarai, Shreehari; Bhatta, Balram; Shrestha, Arjun K.; Kunwar, Ripu M. (Ethnobotany Research and Applications, 2025)
Background: Geographic, cultural, phylogenic, and socio-economic factors influence traditional knowledge. This study evaluates the collection and utilization pattern of the chiuri-Butter tree (Diploknema butyracea (Roxb.) H. J. Lam) across varying geographic and cultural gradients in Nepal. Methods: We carried out a survey of 270 households from nine districts across lowland Tarai, Siwalik, mid-hills, and mountainous physiography covering all regions of western, central, and eastern Nepal. A generalized linear mixed model, ANOVA, and its corresponding post-hoc Tukey test were used to analyze the results. Results: The maximum Use Reports of chiuri were observed for subsistence (1440) followed by primary health care medicine (240), and religious (213). The maximum values of chiuri (Use Reports 402, use value 0.47, and cultural importance index 13.4) were reported from Makawanpur followed by Chitwan, both districts well represent the Central Tarai-Siwalik region. These Use Reports value the chiuri go beyond mere ethnomedicinal. The Chepang ethnic group, inhabiting only the Central Tarai-Siwalik region of the country possesses a rich and diverse knowledge of chiuri collection, utilization, and conservation with a Use Reports of 10.85 per person. Conclusions: Chepang and chiuri are interconnected, as they are associated with most extensive Use Reports. The people have meticulously conserved chiuri trees in their private lands, state forests, and community-based forests. Community-based conservation, local stewardship, and agroforestry policies can ensure sustainable use. Protecting chiuri forests may serve as a vital refuge for the semi-nomadic Chepang, preserving their traditions and livelihoods for future generations. Keywords: Butter tree, Chepang, Ethnoecological knowledge, Socioeconomic attributes